Highly efficient electrocatalytic oxidation of urea on a Mn-incorporated Ni(OH)2/carbon fiber cloth for energy-saving rechargeable Zn–air batteries. Issue 77 (15th September 2017) - Zhang, Xian; Liu, Guoqiang; Zhao, Cuijiao; Wang, Guozhong; Zhang, Yunxia; Zhang, Haimin; Zhao, Huijun
Abstract : The introduction of Mn can effectively regulate the electronic structure of Ni hydroxides on CFC, exhibiting superior electrocatalytic oxidation activity toward urea and potential applications in energy-saving rechargeable Zn–air batteries. Abstract : A Mn-incorporated Ni(OH)2 /carbon fiber cloth (Mn-Ni(OH)2 /CFC) fabricated via a room-temperature solution route exhibited superior electrocatalytic activities of the oxygen reduction and urea oxidation reactions, delivering 12–21% energy saving in the charging process of Mn-Ni(OH)2 /CFC assembled Zn–air batteries in the presence of 0.5 M urea compared to the battery without urea.